{4-Chloro-2′-[(3-methoxy-2-oxidophenyl)-methylidene]benzohydrazido} (pyridine)-copper(II) - Ali, Hapipah Mohd; Yamin, B.M.; Basirun, Wan Jefrey; Khamis, N.A. (International Union of Crystallography, 2004)
In the title compound, [Cu(C15H11ClN 2O3)(C5H5N)], the hydrazide ligand chelates to the central Cu atom in an O,N,O′-tridentate manner and the pyridine molecule coordinates through the N atom, forming a distorted square-planar geometry. The compound has a trans configuration with cis angles about the Cu atom between 81.1 (2) and 95.7 (2)°. The molecule is discrete, with no significant intermolecular interactions. © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.